Impact of the COVID-19 pandemic on prescription drug use and costs in British Columbia: a retrospective interrupted time series study - Kimberlyn McGrail; Sabrina T Wong; Mina Tadrous; Lucy Cheng; Michael Law; Seraphine Zeitouny (BMJ Open)
Objectives To assess the impact of the COVID-19 pandemic on prescription drug use and costs.Design Interrupted time series analysis of comprehensive administrative health data linkages in British Columbia, Canada, from 1 January 2018 to 28 March 2021.Setting Retrospective population-based analysis of all prescription drugs dispensed in community pharmacies and outpatient hospital pharmacies and irrespective of the drug insurance payer.Participants Between 4.30 and 4.37 million individuals (52% women) actively registered with the publicly funded medical services plan.Intervention COVID-19 pandemic and associated mitigation measures.Main outcome measures Weekly dispensing rates and costs, both overall and stratified by therapeutic groups and pharmacological subgroups, before and after the declaration of the public health emergency related to the COVID-19 pandemic. Relative changes in post-COVID-19 outcomes were expressed as ratios of observed to expected rates.Results After the onset of the pandemic and subsequent COVID-19 mitigation measures, overall medication dispensing rates dropped by 2.4% (p<0.01), followed by a sustained weekly increase to return to predicted levels by the end of January 2021. We observed abrupt level decreases in antibacterials (30.3%, p<0.01) and antivirals (22.4%, p<0.01) that remained below counterfactuals over the first year of the pandemic. In contrast, there was a week-to-week trend increase in nervous system drugs, yielding an overall increase of 7.3% (p<0.01). No trend changes in the dispensing of respiratory system agents, ACE inhibitors, antidiabetic drugs and antidepressants were detected.Conclusion The COVID-19 pandemic impact on prescription drug dispensing was heterogeneous across medication subgroups. As data become available, dispensing trends in nervous system agents, antibiotics and antivirals warrant further monitoring and investigation.